К развитию теории телекоммуникационных систем - Поповский, В. В. (ХНУРЭ, 2011)
It is asserted that mathematical models of complex systems, including telecommunication ones, should be built using multidimensional representations. It is interrelation among the components (elements) of the system that assure its super-integral integrity and emergency properties. Two ypes of stochastic systems representations are analyzed: through probabilistic characteristics (of density or of probability distribution function) and through state equations. It is concluded that variable states method is more general and enables to represent all the set of random objects: values, processes and fields.